Practices of Nurses for the Care of Premature in Neonatal Intensive Care Unit: A Literature Review - , Renata Santos Silva, Árgila Gonçalves de Carvalho Santana, Thayná Oliveira Militão, Letícia Gomes de Oliveira, Lilian Clélia Machado Fagundes, Caroline Marinho Pereira, Ludmilla Marinho Maciel, Cláudia Catarina de Andrade Monteiro, Felipe Souza Nascimento, Thifanny Gonçalves de Lira, Larissa Maria Soares Ribeiro, Sarah Nunes Gaia; et al. (Archives of Current Research International, 2020)
Objective: To analyze the nursing care provided to premature infants in the Neonatal Intensive Care Unit. Methods: Descriptive study with a qualitative approach, such as literature review. The selection of articles took place from August to October 2018. The searches resulted in the visualization of 75 articles. Of which only 12 articles met the established criteria and descriptors. Results: The main nursing care provided to premature infants in the NICU are: Observation of the premature infant, in the first 24 hours of life; hydration; food; skin; infection; umbilical stump, among others. Conclusion: When the NB is hospitalized, due to the mother's absence associated with excessive manipulation by the health team, it can trigger stress, impairing her clinical condition. More than technical care is needed, especially by nurses, who are the professionals who most provide care to the newborn in the NICU.